SEMIGROUPS N TIMES INTEGRATED AND AN APPLICATION TO A PROBLEM OF CAUCHY TYPE - Chirinos Fernández, Danessa (2016)
The theory of semigroups n times integrated is a generalization of strongly continuous semigroups, which was developed from 1984, and is widely used for the study of the existence and uniqueness ofproblems such Cauchy in which the operator domain is not necessarily dense. This paper presents an application of semigroups n times integrated into a problem of viscoelasticity, which is formulated as a Cauchy problem on a Banach space presents .